2018
DOI: 10.1002/adfm.201707383
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Ferroelectricity and Antiferroelectricity in Group‐V Monolayer

Abstract: Ferroelectricity is usually found in compound materials composed by different elements. Here, based on first-principles calculations, we reveal the first example of spontaneous electrical polarization and ferroelectricity in stable two-dimensional elemental materials: elemental Group-V (As, Sb, and Bi) monolayers. The polarization is due to the spontaneous lattice distortion with atomic layer buckling.Interestingly, for Bi monolayer, apart from the ferroelectric phase, we find that it can also host an antiferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(139 citation statements)
references
References 39 publications
3
135
1
Order By: Relevance
“…Based on first-principles calculations, Xiao et al revealed robust in-plane ferroelectricity in a family of stable 2D elemental materialsthe monolayers of Group V elements As, Sb, and Bi. 30 These monolayers share similar structures which may be viewed as distorted phosphorene lattice structures with a vertical shift of atoms in each half-layer due to the reduced sp 3 hybridization as compared with P, as shown in Figure 1c. The distortion breaks centrosymmetry and generates a spontaneous in-plane electric polarization, which is robust with polarization values in the order of 10 −10 C/m, and the Curie temperatures estimated to be above room temperature.…”
Section: Intrinsic Ferroelectricity In Van Der Waals Layersmentioning
confidence: 89%
“…Based on first-principles calculations, Xiao et al revealed robust in-plane ferroelectricity in a family of stable 2D elemental materialsthe monolayers of Group V elements As, Sb, and Bi. 30 These monolayers share similar structures which may be viewed as distorted phosphorene lattice structures with a vertical shift of atoms in each half-layer due to the reduced sp 3 hybridization as compared with P, as shown in Figure 1c. The distortion breaks centrosymmetry and generates a spontaneous in-plane electric polarization, which is robust with polarization values in the order of 10 −10 C/m, and the Curie temperatures estimated to be above room temperature.…”
Section: Intrinsic Ferroelectricity In Van Der Waals Layersmentioning
confidence: 89%
“…Among them, buckled (α‐form) and puckered (β‐form) lattices have been noted as most stable for all group V elements, although for arsenene, a γ‐form and a δ‐form has also been proposed. The puckered structure of the group V elemental 2D materials arsenene, bismuthene, and antimonene are predicted to exhibit ferroelectric (and even antiferroelectric in bismuthene) properties with Curie temperature above room temperature, an advancement that, if experimentally realized, would revolutionize the application space of elemental 2D materials . Of the group V elements, air stability remains a common issue.…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%
“…The puckered structure of the group V elemental 2D materials arsenene, bismuthene, and antimonene are predicted to exhibit ferroelectric (and even antiferroelectric in bismuthene) properties with Curie temperature above room temperature, an advancement that, if experimentally realized, would revolutionize the application space of elemental 2D materials. [46] Of the group V elements, air stability remains a common issue. Phosphorene, the puckered or "black" phase, for instance, has been extensively investigated but remains highly susceptible to oxidation in air, making encapsulation schemes necessary.…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%
“…In most cases of MRAMs, the energy cost depends mostly on the first term J for the exchange interaction of adjacent spins, which will be much reduced upon prolonged spin-spin distance (e.g., in diluted magnetic semiconductors [1] ) or when the number of adjacent spins N is reduced in low-dimensions. For example, ferroelectricity (FE) has been recently explored in many 2D materials and revealed to be robust at ambient conditions, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] as summarized in our recent review. As a result, a high Curie temperature can still be maintained when the number of adjacent dipoles is reduced.…”
mentioning
confidence: 99%